Hubungan Peran Tokoh Masyarakat Menurut Remaja dengan Kreativitas Remaja di Kampung Teluk Embun Kabupaten Pasaman - Sinti Alisa; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the decline in activities carried out by adolescents. This was allegedly due to the low role of community leaders in Kampung Teluk Embun, Dua Koto Sub-District, Pasaman Regency. This study aims to (1) describe the role of community leaders towards adolescents, (2) illustrate the creativity of adolescents and (3) see the relationship of the role of community leaders with youth creativity in the Kampung Teluk Embun, Dua Koto Sub-District, Pasaman Regency. This type of research uses correlational quantitative methods. The population in this study were adolescents aged 11-24 years who had not married and lived and had activities in Kampung Teluk Embun, amounting to 29 people. Samples were taken as much as 73%. The number of samples is 21 people. The sampling technique uses simple random sampling. Data collection techniques used are questionnaires. While the data collection tool uses a questionnaire. The data analysis technique of this research uses percentage, rank order and t test. In the results of the study it can be seen that there is a significant relationship between the role of community leaders according to adolescents with adolescent creativity in Kampung Teluk Embun, Dua Koto Sub-District, Pasaman Regency. Keywords: Role, Community Leaders, Creativity, Youth